Análises clinimétricas da versão em português do brasil do questionário emphasis-10 - Sebastião, Vinicius Luiz Guimarães (2020)
INTRODUCTION: Pulmonary hypertension (PH) is a devastating disease characterized by a progressive increase in pulmonary arterial pressure causing failure of the right heart and consequently death. The assessment of health-related quality of life (HRQoL) in these patients are necessary, both to analyze the response to treatment and to monitor the natural evolution of the disease in the patients' quality of life. In Brazil, the questionnaires used to assess a HRQoL of patients with PH are questionnaires adapted from other diseases or generics. EmPHasis-10 is proposed by the literature as a short, multidimensional and easy-to-use questionnaire to assess the QOL of patients with pulmonary hypertension. OBJECTIVE: To perform the clinimetric analyzes of the emPHasis-10 questionnaire, specific to assess a HRQoL of patients with pulmonary hypertension. METHODS: Observational study in which analysis of measurement properties was performed. The emPHasis-10 questionnaire has already been translated and adapted to Brazilian Portuguese. On the first visit, the SF-36 questionnaire was applied, anthropometric data were collected, the emPHasis-10 questionnaire was applied, and the 6-minute walk test was performed. In the second meeting that took place between the 7th and the 14th day, the questionnaire emPHasis-10 was again requested. For the analysis of measurement properties, we follow the methodology suggested by COSMIN (Standards based on consensus for the selection of health measurement instruments). RESULTS: 101 patients were evaluated, 95% of the participants being female and with a mean age of 39.6 ± 11.20 years. In the clinimetric analysis of the questionnaire emPHasis-10, we found that the internal consistency was adequate (Cronbach's alpha: 0.90), with excellent reproducibility (ICC: 0.90 [95% CI: 0.85 - 0.93]). The standard error of measurement was considered very good (EPM: 4.7%). Bland Altman's analysis showed a small mean of the differences (1.04), with a confidence interval (95% CI: -13.19; 15.27). The instrument's validity was considered high for the total score (r: -0.77; p <0.001). The correlation between the total score and the six-minute walk test was considered lower (r: -0.49; p <0.001). No ceiling or floor effect was found in our study. CONCLUSION: emPHasis-10 is considered valid, reliable and has adequate internal consistency to assess QoL of Brazilian patients with PH.